2000
DOI: 10.1021/jf9913155
|View full text |Cite
|
Sign up to set email alerts
|

Partially Carboxymethylated Feather Keratins. 1. Properties in Aqueous Systems

Abstract: Feather keratins were extracted from chicken feathers with an aqueous solution of urea and 2-mercaptoethanol. The keratin solution obtained was dialyzed to remove the reagents. Upon dialysis, extensive protein aggregation occurred. To obtain stable solutions or dispersions in water, cysteine residues were modified prior to dialysis with iodoacetamide, iodoacetic acid, or bromosuccinic acid, thereby blocking free thiol groups and introducing hydrophilic groups. For the development of biodegradable materials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 41 publications
1
107
0
7
Order By: Relevance
“…Although the yield was also high when DTT was used, the solution obtained by this method became partially insoluble after dialysis, so this reducing agent was not suitable. Schrooyen et al [16] reported the yield of keratin extracted from feathers by 2-mercaptoethanol to be approximately 75 %. Poole et al [32] showed that sodium sulphite gave a yield of 62 %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the yield was also high when DTT was used, the solution obtained by this method became partially insoluble after dialysis, so this reducing agent was not suitable. Schrooyen et al [16] reported the yield of keratin extracted from feathers by 2-mercaptoethanol to be approximately 75 %. Poole et al [32] showed that sodium sulphite gave a yield of 62 %.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of keratin by 2-mercaptoethanol, dithiothreitol (DTT) or dithioerythritol, thioglycolic acid, glutathione, sulphites, and bisulphite generates free cysteine residues, and the resulting cysteine-containing derivatives are called ''kerateines'' [7,[15][16][17][18]. They are less polar and more stable in acidic and alkaline solutions than the oxidized derivatives, and they contain amino acid residues capable of re-crosslinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing amount of free sulfhydryl groups (-SH-) in keratin can originate from disruption of the disulfide cysteine bonds (-SS-) induced by radiation. The breaking of all of these disulfide bonds in cysteine, may results in the amount of cysteine equals 720 μmol/g of feathers [13]. Data presented in Figure 5 show that after exposure to 10Gy gamma radiation a sulfohydril group content in hair keratin change insignificantly from 0.21 μmol/g in non-radiated hair to 0.29 μmol/g in irradiated hair, which indicates that only less than 10% of the disulfide bonds were broken.…”
Section: Figure 5 Changes In Content Of Sh-groups Of Human Hair Expomentioning
confidence: 96%
“…The content of free and disulphide bond-forming thiol-containing residues in hydrolyzed keratin was measured by using 2-nitro-5-thiosulphobenzoate and 5,5-diothiobis(2-nitrobenzoic acid) (Ellman's reagent) according to the method of Shrooyen et al [23]. Absorbance measurement was carried out at 412 nm using a TECAN Infinite M200 micro plate reader (Kanagawa, Japan).…”
Section: Content Of Thiol-containing Residues In Hydrolyzed Keratinmentioning
confidence: 99%